ICC 2019 - 2019 IEEE International Conference on Communications (ICC) 2019
DOI: 10.1109/icc.2019.8761782
|View full text |Cite
|
Sign up to set email alerts
|

An SDN-Based Transmission Protocol with In-Path Packet Caching and Retransmission

Abstract: In this paper, a comprehensive software-defined networking (SDN) based transmission protocol (SDTP) is presented for fifth generation (5G) communication networks, where an SDN controller gathers network state information from the physical network to improve data transmission efficiency between end hosts, with in-path packet retransmission. In the SDTP, we first develop a new two-way handshake mechanism for connection establishment between a pair of end host. With the aid of SDN control module, signaling exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The packet drop rate for both the techniques is calculated using the method defined in Reference 42 and verified that our values lie within the acceptable range which is 0%-5%. 43 Figure 13 depicts that through IP address redirection technique 98.5% packets from the attacker network are successfully redirected towards the shadow network/honeynet while only 1.5% packets are dropped and could not reach the shadow network/honeynet. Overall the IP address redirection technique was proved to be successful against attackers.…”
Section: Real Testbeds and Emulationmentioning
confidence: 99%
“…The packet drop rate for both the techniques is calculated using the method defined in Reference 42 and verified that our values lie within the acceptable range which is 0%-5%. 43 Figure 13 depicts that through IP address redirection technique 98.5% packets from the attacker network are successfully redirected towards the shadow network/honeynet while only 1.5% packets are dropped and could not reach the shadow network/honeynet. Overall the IP address redirection technique was proved to be successful against attackers.…”
Section: Real Testbeds and Emulationmentioning
confidence: 99%
“…Each hop requests its upstream ones to feedback the cached packets. J. Chen proposed the adaptive transmission protocol (SDATP) [20] [21]. In the SDATP, each in-path switch retransmits the lost packets detected according to the packet disordering and interarrival time from its upstream neighbored one.…”
Section: Related Workmentioning
confidence: 99%
“…To reduce the EEFR, the current promising approach is hop-by-hop retransmission control for lost packets adopting in-path caching [18] [19] [20] [21] [22]. Recent studies have demonstrated that this type of control can outperform existing end-to-end transport protocols [20] [22].…”
mentioning
confidence: 99%